Occupational tenure in 1987: many workers have remained in their fields. - Carey, Max L. (Monthly Labor Review, 1988)
Occupational tenure information can be useful to individuals, employers, and labor market researchers. As defined by a supplement to the January 1987 Current Population Survey, occupational tenure is the cumulative number of years in which persons have worked in their current occupation, regardless of number of employers, interruptions in employment, or time spent working in other kinds of jobs. Occupational tenure should not be confused with employer tenure, which is the time spent working for the same employer. Several generalizations based on demographic characteristics can be drawn from the January 1987 survey. As might be expected, a worker's average occupational tenure increased with age. Males had more tenure than females, whites more tenure than minorities, and college graduates more tenure than people with less education. The relationship of occupational tenure to various other employment trends is discussed.